Regional innovation performances of firms in Portugal - Vicente Galindo, Purificación (2014)
Portuguese strategic choices on innovation and R&D have led, over the past two decades, to an improved situation of positive achievements, in which the regions of Lisbon and Algarve have taken the lead and are the only ones in the country to converge towards the European average growth rate. Regarding the other Portuguese regions – despite significant national growth rates in the 1990s as well as a successful attempt to cope with the EMU –, these are lagging behind the EU average in what concerns gross production, investment or employment generation. Meanwhile, one of the greatest public policy efforts was to diffuse much of the European funds across the entrepreneurial tissue. After a long pathway, it is now timely to evaluate the firms’ contribution to national and regional growth, their obstacles and impacts.